Using Electronic Resources for Investigating the Impact of COVID-19 on the Mortality Growth in Poland and Ukraine - Puhachova, M. V. (Statistics of Ukraine, 2023)
The occurrence of a new virus that hit the whole world increased the need in not only the processing of the grown scopes of information that had to be used for patient treatment (tracking the course of decease, use of certain drugs, vaccination, death record), but also in creating new online information resources and more intensive use of existing resources (online registers, databases, cadasters, classifiers, etc.) and information systems supporting their operation within and beyond the health care system. Hence, the pandemic proved to be an accelerator of the digitalization of this sphere and other socio-economic sectors. Developed countries have been taking use of high performing systems for online information resources for decades, enabling for accumulating statistical data and making their sound and quick analysis. Ukraine recently has made essential advance on the way to digitalization and, as experts believe, could even outrun Estonia that had been a model example for the majority of European countries in this field. Many countries have created the ground for quick implementation of new online information resources allowing for the storage of all the accumulated information on COVID-19 pandemic. One of these countries is evidently Poland with its rather well-developed system of registers in the health protection system. Large scopes of information about the course of pandemic have been published on various websites of national and foreign organizations engaged in investigating demographic and health care issues. The article contains an analysis of what data about the pandemic, created on the basis of online information resources, is displayed on platforms of international organizations, Poland and Ukraine. A comparison of Poland and Ukraine by some indicators reflecting the spread of coronavirus and fighting with it was made. These indicators include the morbidity, the death toll per million inhabitants, the number of made vaccinations against COVID-19. The study covers the dynamics of a new indicator over the pandemic period, the cruelty index introduced by foreign researchers and used to reveal the reaction of country authorities on the spread of this decease. The article’s objective is to investigate the feasibility of using online resources for analysis of the impact of COVID-19 pandemic on the mortality growth in Poland and Ukraine. The experience of Polish experts was used in providing some recommendations on introducing additional online tools in the Ukrainian health care, in particularly ones designed for predicting epidemic threats and diagnostics of infections.